The Manifestation of 'Urf Concept Based on Local Wisdom in Resolving Marital Conflict Barambangan by Religious Leaders in Banjar Regency - Syafiq, Muhammad; Norwaizi, Ari (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Domestic conflicts known as "Barambangan" in Banjarese society require resolution approaches grounded in local wisdom values. This study aims to analyze the manifestation of the 'urf (customary practice) concept based on local wisdom in resolving marital conflict barambangan by religious leaders in Banjar Regency. This research employs a qualitative method with a sociological-juridical approach, involving six religious leaders from various villages in East Martapura District. Data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that the local 'urf concept manifests in three resolution stages: (1) the listening stage (mamandang), (2) the counseling stage (manasihati), and (3) the mediation stage (mampadamaikan). The local wisdom employed encompasses values such as "bahandap hati" (humility), "bakudutan" (deliberation), and "basalamatan" (prioritizing relationship safety). These findings indicate that the integration of local 'urf with Islamic principles provides effective solutions in domestic conflict resolution, achieving an 80% success rate in preventing divorce. This study contributes to the development of family conflict resolution models based on local wisdom that can be implemented within the context of Islamic family law in Indonesia